2022
DOI: 10.2196/34230
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of Web-Based Interventions to Enhance Resilience in Health Care Professionals: Systematic Review

Abstract: Background Internationally, the impact of continued exposure to workplace environmental and psychological stressors on health care professionals’ mental health is associated with increased depression, substance misuse, sleep disorders, and posttraumatic stress. This can lead to staff burnout, poor quality health care, and reduced patient safety outcomes. Strategies to improve the psychological health and well-being of health care staff have been highlighted as a critical priority worldwide. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Despite this, we managed to recruit on time and reach our target, implement the REsOluTioN program successfully, and collect data at the relevant time points. Hence, our study has provided initial evidence that it is acceptable to implement web-based resilience-enhancement programs with similar design features within busy health care settings; this has been identified in the wider literature prior to the pandemic [ 35 ], but to our knowledge has not been tested since COVID-19. Thus, these findings will enable larger scale studies to test the effectiveness of web-based resilience programs for nurses in terms of increasing resilience and psychological well-being.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite this, we managed to recruit on time and reach our target, implement the REsOluTioN program successfully, and collect data at the relevant time points. Hence, our study has provided initial evidence that it is acceptable to implement web-based resilience-enhancement programs with similar design features within busy health care settings; this has been identified in the wider literature prior to the pandemic [ 35 ], but to our knowledge has not been tested since COVID-19. Thus, these findings will enable larger scale studies to test the effectiveness of web-based resilience programs for nurses in terms of increasing resilience and psychological well-being.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is limited evidence regarding how these benefits are provided and which types of programs work for which staff and in what context. A recent review examining the use of web-based resilience-enhancement interventions showed them to have potential value in clinical practice settings by supporting staff who experienced prolonged workplace stress [ 35 ]. This is particularly important as the development of effective and evidence-based web-based programs can play a vital role in the current pandemic climate, where face-to-face training or meetings are often restricted or not allowed [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging research from the COVID-19 pandemic suggests a similar or worse trajectory (2,4). Facilitating access to effective treatment and psychosocial support is critical to mitigating negative impacts on mental health, minimizing distress, and reducing burnout (5,6).…”
Section: Introductionmentioning
confidence: 99%